New cases of jaundice due to pedicular neoplastic lymphadenopathy - Lyonnet, Alberto; Tiscornia, Eduardo; D'Auria, Agustín; Nuchowich, Gustavo; Cilleruelo, Roberto; Pomi, Jorge; Estefan, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1986)
Presentation of 9 new observations of obstruclive jaundice by neoplasic adenopathies of the hepatic pedicle secondary to non biliary or pancreatic cases. This statistical data complements a former work published by the author in 1981 and ratifies the statistical conclusions of same in respect of the seriousness of this condition, a long with the posibility in not very old patients of performing a paliative derivative operation with fairly acceptable results. Percutaneous transhepatic transtumoral intubation is a less complicate new method that has been used in two of the above observations.